The Contribution of the TNI Manunggal Membangun Desa Program to Community Welfare in Indonesia - Mohammad Zaini; Alfitri Alfitri; Andries Lionardo; Sena Putra Prabujaya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to explore the contribution of the TNI Manunggal Membangun Desa (TMMD) program to community welfare in Indonesia and to propose a new conceptual framework for optimizing the implementation of TMMD based on the principles of New Public Management (NPM). The research employs a qualitative approach, utilizing both primary and secondary data sources, which are analyzed through thematic analysis to identify key patterns and themes in the implementation of TMMD. The main theoretical framework applied in this study is New Public Management, which is used to examine the managerial transformation and governance of TMMD as a performance- and results-oriented development program. The findings indicate that TMMD has implicitly adopted several NPM principles, including professionalized management, impact-based performance measurement, outcome-oriented service delivery, organizational specialization, cross-sectoral collaboration, and disciplined and efficient resource management. These practices have enhanced program effectiveness and generated tangible socio-economic benefits for local communities. Based on these findings, this study proposes an optimization framework that positions TMMD as a collaborative, accountable, and results-oriented public policy instrument, contributing both theoretically and practically to the discourse on results-based governance and development in the public sector.